An efficient zinc-catalyzed cross-coupling reaction of aryl iodides with terminal aromatic alkynes. Issue 41 (7th October 2015) - Thankachan, Amrutha P.; Sindhu, K.S.; Krishnan, K. Keerthi; Anilkumar, Gopinathan
Graphical abstract: The first Zn-catalyzed protocol for the Sonogashira-type cross-coupling reactions for the synthesis of diaryl substituted alkynes is described. Abstract: The first Zn-catalyzed protocol for C(sp 2 )–C(sp) cross-coupling reactions for the synthesis of disubstituted alkynes is described. A broad spectrum of functional groups is tolerated during the catalysis and successfully afforded a variety of diaryl substituted acetylenes.